SMART NUTRITION SCALE UNTUK DETEKSI GIZI BAYI DAN REKOMENDASI MPASI OTOMATIS - Retno Sukmaningrum; Agrippina Waya Rahmaning; Haninda Agyanti F (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
Abstract - Monitoring the nutritional status of infants aged 6 to 12 months is crucial, as it has a direct impact on physical growth, cognitive development, and overall health. This study introduces a Smart Nutrition Scale designed around an ESP32 microcontroller. It incorporates a load cell sensor for measuring body weight and a rotary encoder for detecting body length. The system automatically processes the measurement data using anthropometric parameters and WHO Z-score standards to classify nutritional status. It then generates personalized complementary feeding (MPASI) recommendations based on the infant’s age, sex, and nutritional category, detailing the daily requirements for carbohydrates, proteins, and fats. The results of the measurements and the recommendations are displayed on an LCD screen and a connected web interface via Firebase. Accuracy tests demonstrate a weight measurement precision of 96.48% and a length accuracy of 99.71%. This innovative system serves as a practical and accessible tool to assist parents and healthcare professionals in early nutritional screening and guidance for complementary feeding.